Pembelajaran Sastra dan Daya Nalar Siswa - Dinda Luthfia; Siti Rukiyah; Missriani M (Yayasan Daarul Huda Kruengmane, 2023)
One aspect that is considered less than optimal in the educational process in schools today is literature learning. In fact, literature learning can be a means of developing students reasoning, creativity, personal maturity and social skills. To realize the ideals of literary learning, a change in the literary learning paradigm is needed, both theoretically and conceptually, as well as from the technical aspects of implementation, such as methods, strategies, materials, presentation steps, learning media, evaluation, and more importantly the formulation of teaching objectives. All technical components must be designed in such a way that literature learning can actually be a means of increasing students' reasoning power and creativity.